#### Answer

$=17-6x$

#### Work Step by Step

$ 7 + 2[3(x + 1) - 2(3x - 1)]$
$=7+2[3x+3-6x+2]$
$=7+2[-3x+5]$
$=7-6x+10$
$=17-6x$

Published by
Pearson

ISBN 10:
0-13446-914-3

ISBN 13:
978-0-13446-914-0

$=17-6x$

$ 7 + 2[3(x + 1) - 2(3x - 1)]$
$=7+2[3x+3-6x+2]$
$=7+2[-3x+5]$
$=7-6x+10$
$=17-6x$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.